Pengaruh Gaya Kepemimpinan Dan Motivasi Terhadap Kinerja Karyawan Pada PT. Citra Indojaya Perkasa - Linda Linda; Ani Rakhmanita (Politeknik Kampar, 2023)
Good employee performance can be determined by applying the right leadership style and motivation, because by providing the right leadership style and motivation to employees will make employees have high motivation so as to produce quality employee performance. Based on a survey of researchers directly that according to employees of PT. Citra Indojaya Perkasa led by PT. Citra Indojaya Perkasa does not listen to the opinions of its employees and the motivation given by the company to employees must be maintained because it is to maintain effectiveness and achieve the company's vision and mission. The purpose of this study is to determine the influence of Leadership Style (X1) and Motivation (X2) on Employee Performance (Y) in the Security Division of PT. Citra Indojaya Perkasa. In this study using Quantitative Statistics method. After the calculations were carried out through SPSS it was known that the results of this study stated that the variables of Leadership Style and Motivation simultaneously had an effect on employee performance. Thus it can be stated that the motivational variable cannot stand alone, the existence of a good leadership style can affect the motivation of its employees.